Analisis Yuridis Penguatan Hak Sipil dan Ekonomi Perempuan Berdasarkan Prinsip Astacita Keempat dalam Hukum Perdata Indonesia - Waris, Asriyuni; Ambo, Siti Halmaira; Moonti, Roy Marthen (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This study conducts a juridical analysis of the strengthening of women's civil and economic rights in Indonesian civil law, based on the 4th Astacita principle of women's empowerment. The study identifies and analyzes inequalities in women's access to civil rights, such as inheritance rights, property ownership, and social security. Although the national legal framework has recognized the principle of gender equality, its implementation still faces significant challenges due to the strong patriarchal culture and women's limited access to legal justice. Therefore, this study emphasizes the urgency of gender-responsive legal reforms and increased women's participation in the legislative process to realize substantive equality and justice.